Identity of Self and Other in Paradise Lost by John Milton: An Oriental Study - Samina Yasmin; Mehr-ul-Nisa; Aqsa Nawaz (ACADEMIA International Journal for Social Sciences, 2025)
This research shows how literature perpetuated dominant power structures and established cultural definitions of identity and otherness across historical contexts. The paper applied Edward Said’s theory of Orientalism to study Milton’s Paradise Lost (1667) in the context of epic literature displaying new hierarchies of power, civilization, and knowledge parallel to later colonial discourse. To achieve this purpose, this work reinterprets Adam and Eve as the innocent, subservient, and somewhat naïve eastern "Other" as well as, Satan as the rational, ambitious, and dominating western "Self." It shows that Milton's construction of inferiority and superiority take-off the ideological structures critiqued by Said. The analysis refocused on such issues as they prevail against margin dynamic, the binary opposition of civilization against barbarism, and various Western misconceptions of the East, including the depictions of matrimony and gender roles. Such ideologies found in Paradise Lost resonate with Orientalism as justifications for colonial rule, even though this epic was written before Western expansion into the colonies.